Magnetoelectric coupling studies in lead-free multiferroic (Ba0.85Ca0.15)(Zr0.1Ti0.9)O3−(Ni0.7Zn0.3)Fe2O4 ceramic composites. Issue 17 (1st September 2022) - Coondoo, Indrani; Vidal, João; Bdikin, Igor; Surmenev, R.; Kholkin, Andrei L.
Abstract: Lead-free multiferroic 3–0 type particulate composites with a composition (1− x )(Ba0.85 Ca0.15 Zr0.1 Ti0.9 O3 ) – x (Ni0.7 Zn0.3 Fe2 O4 ) [(1− x )BCZT – x NZFO with 0 ≤ x ≤ 100 at%] were prepared using solid state reaction method. Structural and microstructural analysis using XRD, FESEM and Raman techniques confirmed the phase formation of the ferroelectric (BCZT) and magnetostrictive (NZFO) phases without any detectable presence of impurity phases. Rietveld refinement of the XRD data revealed a tetragonal ( P 4mm) and a cubic structure ( F d 3 ‾ m) for the BCZT and NZFO phases, respectively. Elemental compositions of the constituent phases were assessed by EDS and XPS analyses. Electrical, magnetic, and magnetoelectric (ME) measurements were performed. The composites exhibit typical well-saturated magnetic hysteresis ( M −H) loops at room temperature, having very low coercive field ( H C ) values, indicating their soft ferromagnetic behavior. Various parameters extracted from the M−H curves including H C, magneto-crystalline anisotropy, squareness, and magnetization were found to depend on x. Frequency dependence of capacitance and admittance exhibited a resonance behavior corresponding to the radial mode of the electromechanical resonance (EMR). ME coefficients were studied in both longitudinal ( α E 33 ) and transverse ( α E 31 ) modes. The highest coupling coefficients, α E 31 ∼14.5 mV/Oe.cm and α E 33 ∼13 mV/Oe.cm were obtained for composite with 50 at% NZF at off -resonance frequency of 1 kHz. At the EMR frequency of 314 kHz, the α E 31 value in 0.5BCZT-0.5NZFO composite enhanced enormously to ∼5.5 V/Oe.cm. The studies conclude that x = 0.5 is an optimum atomic fraction of NZFO in the particulate composite for maximum ME coupling.